El adjetivo maiestus, -a, -um. Iosephus I. Scaliger y Thomas Munckerus. - Moya del Baño, Francisca (Myrtia, 2025)
The article focuses on the adjective "maiestus," used by Iosephus Iustus Scaliger and Thomas Munckerus in the context of the translation of the Hymni Orphici and Petronius's Satyricon. It analyzes the evolution and use of this term in Latin literature, highlighting Quevedo's criticism of Scaliger's translations and Munckerus's proposal of the form "majesto." The author explores the relationship of "maiestus" with other Latin terms and its possible meaning, as well as its presence in dictionaries and later editions. It concludes that, although there is no absolute certainty about its use, the existence of the adjective in the Latin language is supported by the work of these philologists.